Construction and comprehensive analysis of DNA methylome in Pandoraea spp. at single base resolution / Lim Yan Lue - Lim , Yan Lue (2018)
Prokaryotic DNA methylation is a prevalent epigenetic modification on bacterial DNA bases and is accomplished by DNA methyltransferases which catalyse covalent attachment of methyl groups onto the DNA bases. DNA methylation of prokaryotic genomes, in particular those catalysed by solitary DNA methyltransferases, were demonstrated to contribute to regulation of a plethora of cellular processes including gene expression regulation, DNA replication control, DNA mismatch repair and pathogenicity. However, despite the expansion of prokaryotic epigenetic studies in recent years, characterisation of DNA methylation, especially in the beta-subclass of Proteobacteria and environmental isolates largely remain unexploited to date. Therefore, this dissertation aims to characterise the epigenomic landscape of the genus of Pandoraea, a newly described taxa in Betaproteobacteria. Members of Pandoraea are frequently reported as emerging opportunistic pathogens with multi-drug resistance properties. To date, no methylome studies were performed on these bacterium. Single Molecule Real Time (SMRT) sequencing technology was employed to perform complete genome sequencing and detection of epigenetic modifications at base-pair resolution on 10 Pandoraea strains, b inclusive of 9 type strains acquired from the Leibniz-Institut DSMZ culture collection centre (Pandoraea apista DSM 16535T, Pandoraea faecigallinarum DSM 23572T, Pandoraea norimbergensis DSM 11628T, Pandoraea oxalativorans DSM 23570T, Pandoraea pnomenusa DSM 16536T, Pandoraea pulmonicola DSM 16583T, Pandoraea sputorum DSM 21091T, Pandoraea thiooxydans DSM 25325T, and Pandoraea vervacti DSM 23571T) and 1 in-house landfill isolate, Pandoraea pnomenusa strain RB-38. From the whole-genome methylation patterns analysis, 1 palindromic N6-methyladenine (m6A) sequence motif, GTWWAC, was identified in the genomes of all 10 Pandoraea strains. Furthermore, from the restriction-modification (R-M) system genes annotation performed, a Type II orphan methyltransferase, was identified to be the corresponding methyltransferase of the conserved motif detected. Subsequent bioinformatics analysesperformed indicated that the candidate methyltransferase represents a novel class of orphan methyltransferase within the family of Burkholderiaceae and Oxalabacteraceae. Comparative genome-wide GTWWAC methylation pattern distribution analysis performed indicated that this methyltransferase, currently designated as Pandoraea adenine methylase (PAM), demonstrated analogous function with Dam (DNA adenine methyltransferase) and CcrM (cell-cycle regulated methyltransferase), both are well characterised orphan methyltransferases prevalent in Gammaproteobacteria and Alphaproteobacteria respectively. In conclusion, in addition to providing the first comprehensive illustration of the pan-genus methylome profile of Pandoraea, the findings of this dissertation also reported the identification of a potential novel class of orphan methyltransferase within the class of Betaproteobacteria.